High‐Efficient Charge Generation in Single‐Donor‐Component‐Based p‐i‐n Structure Organic Solar Cells. Issue 4 (5th February 2020) - Zhang, Yajie; Deng, Dan; Wu, Qiong; Mi, Yang; Yang, Chen; Zhang, Xuning; Yang, Yang; Zou, Wenjun; Zhang, Jianqi; Zhu, Lingyun; Zhou, Huiqiong; Liu, Xinfeng; et al.
Abstract : Organic solar cells (OSCs) require a bulk heterojunction of a donor and an acceptor for efficient charge generation, whereas other types of solar cells normally use the p‐i‐n device structure. Herein, a comparative investigation of the p‐i‐n‐structured OSCs is conducted based on single‐donor‐component BTID‐0F and the bulkheterojuction OSCs with different donor:acceptor blend ratios using BTID‐0F as the donor and PC71 BM as the acceptor. The highest power conversion efficiency (PCE) of 1.61% is obtained for single‐donor‐based OSCs. The impact of PC71 BM weight ratio in BTID‐0F:PC71 BM‐based OSCs upon blend morphology, material energetics, photogenerated charge dynamic process, and photovoltaic device performance is investigated, and the highest PCE reaches 8.47%. Results indicate that even when the acceptor sites are highly diluted and the acceptor phase is discontinuous, electron transport can occur with a reasonable electron mobility. The PCE of 1.61% is the highest PCE reported for p‐i‐n structure OSCs based on a single‐donor component, which is helpful to understand the mechanism of charge generation in organic materials and thus obtainhigh‐efficient OSCs using the p‐i‐n structure. Abstract : A comparative investigation of single‐donor component and different donor:acceptor blend ratio‐based organic solar cells (OSCs) is conducted using BTID‐0F as the donor and PC71 BM as the acceptor. The highest PCEs of 1.61% for single‐donor and 8.47% for BTID‐0F:PC71 BM‐based OSCs are obtained. Herein, the mechanism of charge generation in organic materials, thus obtaining high‐efficient single‐component OSCs, is analyzed.